MANAJEMEN LAYANAN BIMBINGAN DAN KONSELING BAGI SISWA BROKEN HOME MELALUI PENDEKATAN ASWAJA [MANAGEMENT OF GUIDANCE AND COUNSELING SERVICES FOR BROKEN HOME STUDENTS THROUGHT THE ASWAJA APPROACH] - Ani Sri Nurhayati; Abu Darim; Mauhibur Rokhman (Perkumpulan Ahli Bimbingan Konseling Islam (PABKI) Indonesia, 2021)
The purpose of this research is to discuss planning, organizing, and implementing counseling services for broken home students through the Aswaja approach. This article uses a type of qualitative research with a case study approach. In this research, data collection techniques with observation, interviews, and documentation. In data analysis, the researcher went through the stages of data reduction, presenting the data, and concluding the data. The researcher validated the data obtained using triangulation of techniques and sources. The findings in this research consist of: First, guidance and counseling teachers plan counseling services by making needs analysis, work programs, and activity plans. Second, guidance and counseling teachers organize their activity plans in coordination with the homeroom teacher. The things discussed were the majority of problems that arose in the previous year and the selection of the Aswaja approach as a treatment for the aspirations and input of stakeholders. Third, guidance and counseling teachers carry out counseling services at any time when problems arise, regardless of the schedule of activities made. Fourth, guidance and counseling teachers encounter obstacles in the form of not having special time for counseling services and having to take active lesson hours, while the supporting factors for implementing the Aswaja approach cannot be separated from the support of homeroom teachers and religious teachers.